Deterioration of the Internal Structure of Loess under Dry-Wet Cycles. (16th July 2020) - Ye, Wanjun; Bai, Yang; Cui, Chenyang; Duan, Xu
Abstract : To understand the structural damage evolution process of loess under the action of dry-wet cycles, a triaxial test of a dry-wet cycle was performed by considering three influencing factors: initial moisture content, amplitude of the dry-wet cycle, and number of dry-wet cycles. The stress-strain curves of undisturbed loess samples at different cycling times vary under different compacted loess cycles. Under the same axial strain, the stress value of the undisturbed loess is higher than that of the loess sample after a dry-wet cycle, indicating that such cycle can reduce the strength of loess. As the number and amplitude of dry-wet cycles increase, the shear strength of the loess sample and the value of cohesion ( c ) of the strength index gradually decrease, and the amplitude gradually decreases. With an increase in the number and amplitude of dry-wet cycles, the change in the internal friction angle of the strength index is inevident, indicating that the effect of dry-wet cycles on the internal friction angle of loess is insignificant. Computed tomography (CT) scan experiments were also conducted to obtain the evolution of loess cracks before and after a dry-wet cycle. Studies have shown that as the number and amplitude of dry-wet cycles increase, the mean (ME) value of CT decreases, the standard deviation (SD) value increases, and the ME value is obtained during the initial stage of a dry-wet cycle. Meanwhile, the decreasing trend of ME and the increasing trend of SD values are most evident during the period of a dry-wet cycle. In conclusion, dry-wet cycles promote the development of cracks.